A general fixed point theorem for implicit cyclic multi-valued contraction mappings - Popa, Valeriu (Annales Mathematicae Silesianae, 2015)
In this paper, a general fixed point theorem for cyclic multi-valued mappings satisfying an implicit relation from [19] different from implicit relations used in [13] and [23], generalizing some results from [22], [15], [13], [14], [16], [10] and from other papers, is proved.